Solubility of gemcitabine (an anticancer drug) in supercritical carbon dioxide green solvent: Experimental measurement and thermodynamic modeling - Gholamhossein Sodeifian; Masturah Markom; Jarinah Mohd Ali; Muhammad Zulhaziman Mat Salleh; Reza Derakhsheshpour (Scientific Reports)
Abstract In order to develop supercritical fluid (SCF) processes for the micro or nanosizing of solid solute components, such as pharmaceuticals, it is essential to assess their solubility in solvents including supercritical carbon dioxide (SC–CO2). This crucial step is fundamental for choosing and evaluating the processes in SCF technology. A statistical method was developed and used to determine the solubility of gemcitabine in SC-CO2. The solubility measurements at various pressures and temperatures were conducted using UV–vis analysis. Two model types were used to correlate the data: semi-empirical (with 3–6 parameters) and equation of state (EoS) models. The solubility of gemcitabine in SC-CO2 using a static method at temperatures of 308–338 K and pressures of 120–270 bar were measured and modeled for the first time. Solubility of gemcitabine ranged from 0.1274 × 10− 5 to 1.8128 × 10− 5 in mole fraction and 0.00295 to 0.08489 kg/L. The PR EoS model performed best at 308 K with an AARD of 12.58%, and SRK excelled at 318–338 K with AARDs between 12.93 and 15.68%. Application of the Joback method (AARD 12.04–27.13%) and COSMO-RS method (AARD 18.68–31.28%) in EoS models also were compared. The Bian et al. model showed the best fit among density-based models with an AARD of 16.62%.